Perancangan Interior Pusat Pelatihan Aikijujutsu Take Sogo Budo di Surabaya - Tejo, Jemmy Hartawan (Intra, 2013)
Interior Designing Training Center of Aikijujutsu Take Sogo Budo in Surabaya is intended to provide all facilities that associated with the sport needs of Aikijujutsu with international standards, so that it can be proper to be used as a Aikijujutsu sport center. Besides, it also provided some supporting facilities such as galleries, shops and office in order to facilitate all the needs of the practitioners of Aikijujutsu. To show the characteristic of Aikijujutsu that quiet, dynamic, assertive and disciplined, therefore this design concept using Japanese traditional style and modern style in order to create an impression of a country where the sport originated and in accordance with the dynamic characteristics of Aikijujutsu. The application of traditional Japanese style seen in the design style that looks simple and functional, the colors that used leads to natural modern color to adjust with the Japanese traditional style that also dominant with natural colors.